Bio-Activity of Some Oil extracts on Khapra Beetle Trogoderma gronarium Everst (Cloptera:Dermastidae) larvae on Barley seeds Hordeum vulgare (Journal of the College of Basic Education, 2022)
The effect of some plant oils on Trogoderma granarium larvae was investigated in the laboratory at 27±2 Co and 70% Relative humidity on barley grains 10 grams of barley were treated with five different concentration of plant oils (Eugenia caryophyllata, Osimum basilicum,Piper nigrum, and Azadirachta indica). The results showed that the rate of mortality was reached 99.96% and 93.33% when grain treated with 12.5% of A.indica and P.nigrum respectively. Also the results indicated that using 12.5% of O.basilicum and A indica reduce the germination of barley grains after treating with plant olis up to 26.66%.So it can be considred that these plant oils an environmentily safe and cheap inproteting the darley grains from infestation by T.granarium and used an alternative to chemical insecticides